BOUNDARY ELEMENTS MODELLING FOR SMALL/LARGE STRAIN ANALYSIS OF ELASTOMERIC MATERIALS (Journal of Engineering, 2010)
In this paper the boundary elements method is used as numerical techniques for solving elastomeric materials (rubber or rubber-like materials) under small and large strains analysis. Under small deformations, the formulations are based on assuming that the elastomer is linear elastic isotropic incompressible solid. While for the large deformation, the formulation is based on decomposing the 1st Piola-Kirchhoff stresses into linear and nonlinear parts. Thereafter, the final derived equations are composed of both boundary integral and non-linear domain integrals. The non-linear analyses were performed using an incremental procedure with an iterative algorithm.Solving some numerical examples and comparing the results with that obtained from some available results and ANSYS 10.0 showed that the boundary elements method is a good numerical technique for solving incompressible elastomeric materials. And the formulation used for the boundary elements derivations for large strain analysis gave satisfactory results as compared with that of ANSYS ver. 10.0.